2012
DOI: 10.4269/ajtmh.2012.12-0100
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Granulomatous Amoebic Encephalitis with Voriconazole and Miltefosine in an Immunocompetent Soldier

Abstract: Abstract.A 38-year-old male immunocompetent soldier developed generalized seizures. He underwent surgical debulking and a progressive demyelinating pseudotumor was identified. Serology and molecular testing confirmed a diagnosis of granulomatous amoebic encephalitis caused by Acanthamoeba sp. in this immunocompetent male. The patient was treated with oral voriconazole and miltefosine with Acanthamoeba titers returning to control levels and serial imaging demonstrating resolution of the residual lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…However, substantial miltefosine concentrations were demonstrated in the brain parenchyma and CSF of patients treated for Balamuthia and Naegleria infections (Schuster et al, 2006). Furthermore, Webster et al (2012) reported successful treatment of immune-comptent patient with granulomatous amoebic encephalitis caused by Acanthamoeba spp. with oral miltefosine.…”
Section: Introductionmentioning
confidence: 97%
“…However, substantial miltefosine concentrations were demonstrated in the brain parenchyma and CSF of patients treated for Balamuthia and Naegleria infections (Schuster et al, 2006). Furthermore, Webster et al (2012) reported successful treatment of immune-comptent patient with granulomatous amoebic encephalitis caused by Acanthamoeba spp. with oral miltefosine.…”
Section: Introductionmentioning
confidence: 97%
“…However, these regimens exhibit poor efficacy because under adverse conditions Acanthamoeba trophozoites can convert to a protective cyst form, which is resistant to antimicrobial agents. Moreover, no effective treatment has been established for GAE, although a few cases have been successfully treated using chemotherapy with sulfadiazine (combined with ketoconazole or fluconazole), voriconazole, and miltefosine (7,8). Thus, development of novel therapeutic agents against Acanthamoeba should be focused on the critical targets involved in cellular metabolism, viability, or pathogenicity.…”
mentioning
confidence: 99%
“…While this antimicrobial treatment can kill the trophozoites, the resistance of Acanthamoeba cysts to antimicrobials can lead to the recurrence of keratitis. For GAE, combination therapies were found more successful than single-drug therapies, and therefore, current therapeutic agents include a combination of ketoconazole, fluconazole, itraconazole, pentamidine isethionate, sulfadiazine, amphotericin B, azithromycin, rifampin, voriconazole, and miltefosine (12)(13)(14)(15). Because of the lack of optimal antimicrobial therapy, GAE is often fatal, and fewer than 10 GAE patients have been successfully treated with multidrug regimens (16).…”
mentioning
confidence: 99%